2021
DOI: 10.3389/fcell.2021.737003
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Attenuates Chronic Stress-Induced Cardiomyopathy by Adaptively Regulating Macrophage Polarizations via β2-Adrenergic Receptor Modulation

Abstract: Clinical demographics have demonstrated that postmenopausal women are predisposed to chronic stress-induced cardiomyopathy (CSC) and this has been associated with the decrease of estrogen. Meanwhile, recent studies have implicated unsolved myocardial proinflammatory responses, which are characterized by enormous CD86+ macrophage infiltrations as an underlying disease mechanism expediting the pathological remodeling of the heart during chronic stress. However, we had previously demonstrated that estrogen confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Chronic stress has been demonstrated to increase myocardial inflammation, a mediator in the progression of heart failure [ 22 ]. Hence, we assessed the effect of E2 on myocardial inflammatory response during CCS.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic stress has been demonstrated to increase myocardial inflammation, a mediator in the progression of heart failure [ 22 ]. Hence, we assessed the effect of E2 on myocardial inflammatory response during CCS.…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to investigate HFpEF, several animal models have been used including the bilateral oophorectomy (OVX) in rats, which provides a valuable model of hypertrophy and HF and allows the investigation of the role of estrogen-induced cardioprotection [ 30 ]. Comorbidities associated with female aging were evaluated in the OVX model which was also been linked to high blood pressure [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], volume overload [ 40 , 41 ], metabolic syndrome [ 42 , 43 , 44 ], type 2 diabetes (T2DM) [ 45 , 46 , 47 , 48 , 49 ] and stress [ 25 , 50 , 51 ].…”
Section: Mechanism Of Menopause-induced Hfpef and Targets For Treatmentmentioning
confidence: 99%
“…The presence/supplementation of E2 during stress avoids all adverse effects of chronic stress, while preventing excessive β2AR depletion. Furthermore, E2 facilitates the resolution of the myocardial inflammatory response by facilitating a reparative response [ 51 ].…”
Section: Mechanism Of Menopause-induced Hfpef and Targets For Treatmentmentioning
confidence: 99%
“…Studies show that activated NF-κB can stimulate the intrinsic apoptotic pathway in the mitochondria via releasing cytochrome c, which triggers caspase cascades resulting in programmed cell death ( Liu et al, 2004 ; Albensi, 2019 ; Adu-Amankwaah et al, 2021a ; Figure 3 ). Irrefutably, increased levels of TNFα in the stress state has been linked to the pathophysiology of heart failure development in various clinical investigations ( Ferrari et al, 1995 ; De Biase et al, 2003 ; Dunlay et al, 2008 ) and animal models ( Bozkurt et al, 1998 ; Bryant et al, 1998 ; Moe et al, 2004 ; Guggilam et al, 2007 ; Adzika et al, 2021 ; Hou H. et al, 2021 ). For instance, a study carried out by Bryant et al reveals that cardiac myocytes’ overproduction of TNFα is sufficient to cause heart failure, implying that this cytokine plays a causative role in the development of heart failure ( Bryant et al, 1998 ).…”
Section: A Disintegrin and Metalloprotease 17 In Cardiac Inflammationmentioning
confidence: 99%
“…Furthermore, many animal studies have demonstrated that in a stress state, upregulated levels of IL-6 in myocardia enhance the development of heart failure while its inhibition improves cardiac function. ( Lai et al, 2012 ; Zhao et al, 2016 ; Adzika et al, 2021 ; Hou H. et al, 2021 ; Huo S. et al, 2021 ).…”
Section: A Disintegrin and Metalloprotease 17 In Cardiac Inflammationmentioning
confidence: 99%